2005
DOI: 10.1103/physrevb.72.125428
|View full text |Cite
|
Sign up to set email alerts
|

Stability of carbon nanotubes under electron irradiation: Role of tube diameter and chirality

Abstract: As recent experiments demonstrate, the inner shells of multiwalled carbon nanotubes are more sensitive to electron irradiation than the outer shells. To understand the origin of such counterintuitive behavior, we employ a density-functional-theory based tight-binding method and calculate the displacement threshold energies for carbon atoms in single-walled nanotubes with different diameters and chiralities. We show that the displacement energy and the defect production rate strongly depend on the diameter of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 32 publications
9
122
1
2
Order By: Relevance
“…This value ͑perpendicular direction͒ was very close to the corresponding value for graphite ͑15-20 eV͒. 72 Later calculations 46,210 showed that for small nanotubes with diameters less than 1 nm, T d indeed depends on the tube diameter and chirality. Figure 13 shows T d as a function of tube diameter for armchair nanotubes.…”
Section: Carbon Atom Displacement Energysupporting
confidence: 58%
See 3 more Smart Citations
“…This value ͑perpendicular direction͒ was very close to the corresponding value for graphite ͑15-20 eV͒. 72 Later calculations 46,210 showed that for small nanotubes with diameters less than 1 nm, T d indeed depends on the tube diameter and chirality. Figure 13 shows T d as a function of tube diameter for armchair nanotubes.…”
Section: Carbon Atom Displacement Energysupporting
confidence: 58%
“…A nonorthogonal self-consistent charge TB method 208,209 in which the parameters of the Hamiltonian were derived from DFT calculations ͑a second-order expansion of the KohnSham total energy in DFT with respect to charge density fluctuations͒ has been widely used for simulations of impacts of energetic electrons onto C, 46,210,211 BN, 212 and SiC ͑Ref. 213͒ nanosystems.…”
Section: E Tight-binding Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 In the present energy range, energy dissipation in matter by electron beams is almost exclusively due to inelastic electron-electron scattering. Elastic electron scattering by target nuclei, well-known to be responsible for irradiation damage via knock-on atomic displacement at high beam energies (above about 80 keV for CNTs), 12,13 results in significant momentum transfer (or equivalent, angular deflection) but practically zero energy loss. 14 Contrary to the continuous energy-loss models (e.g., from stopping power theory) widely used for studying irradiation effects in bulk solids, MC models of materials with restricted dimensions (e.g., CNTs and nanodevices in general) must account for secondary-electron cascade generation through the use of discrete (or single-scattering) energy-loss models.…”
mentioning
confidence: 99%